2018
DOI: 10.1111/anae.14415
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rate of injection on injection pressure profiles measured using in‐line and needle‐tip sensors: an in‐vitro study

Abstract: Alongside ultrasonic visualisation, measurement of injection pressure is an effective tool for reducing the risk of intraneural injection during peripheral nerve block. The aim of this study was to compare injection pressure profiles when measured along the injection line with the pressure measured directly at the needle tip using different rates of injection. A syringe pump delivered a 5-ml injection of saline into silicone gel at three different speeds (5 ml.min , 10 ml.min and 15 ml.min ). Fibreoptic pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…In past issues and this issue of Anaesthesia , a group of Swiss and French colleagues share with us their findings following a series of in‐vitro and ex‐vivo investigations on injection pressure measurement in needles and injection assemblies used for peripheral regional anaesthesia. The authors first described and validated a novel system for real‐time continuous monitoring of injection pressure at the needle tip using an optical fibre pressure sensor, as compared with conventional in‐line monitors .…”
Section: What Is New?mentioning
confidence: 99%
See 1 more Smart Citation
“…In past issues and this issue of Anaesthesia , a group of Swiss and French colleagues share with us their findings following a series of in‐vitro and ex‐vivo investigations on injection pressure measurement in needles and injection assemblies used for peripheral regional anaesthesia. The authors first described and validated a novel system for real‐time continuous monitoring of injection pressure at the needle tip using an optical fibre pressure sensor, as compared with conventional in‐line monitors .…”
Section: What Is New?mentioning
confidence: 99%
“…This difference was especially striking when the rates of injection were increased. In contrast, the pressure measured at the needle tip was not influenced by the speed of injection . Saporito et al are to be commended for their new and fresh look at injection pressure monitoring.…”
Section: What Is New?mentioning
confidence: 99%
“…5,6 However, when measured along the injection line, injection pressure is influenced by the characteristics of the injection system and its parameters; namely the speed of injection, the size of the needle and the size of the connection tube. [7][8][9] Moreover we have previously shown that the actual injection pressure value at the needle tip cannot be deduced from the values measured along the line, since the gap between these two values is not constant, being a resultant of the compliance of the whole system. 8 We have also proven experimentally that only when measured at the needle tip level, injection pressure is independent of the speed of injection.…”
Section: Introductionmentioning
confidence: 99%
“…8 We have also proven experimentally that only when measured at the needle tip level, injection pressure is independent of the speed of injection. 9 Therefore the 103.42 kPa (15 psi) in-line threshold safety standard currently accepted shall be reconsidered. In order to be accurate and reproducible with any injection system and non operator-dependent, injection pressure has thus to be measured at the needle tip level.…”
Section: Introductionmentioning
confidence: 99%
“…Injection pressure can indicate intraneural injection, even where ultrasound and nerve stimulation do not, reducing further the likelihood of inaccurate needle tip placement, and therefore catastrophic complication . The sensitivity and specificity of real‐time injection pressure curves are greatly improved at the needle tip, hence our use of a new system in recent studies which we think is likely to improve the safety of regional anaesthesia still further .…”
mentioning
confidence: 99%